Konstitusionalitas Mengenai Kekuasaan Negara dalam Kegiatan Penanaman Modal (Analisis Putusan MK No. 21- 22/PUU-V/2007) - Muda, Iskandar (Mahkamah Konstitusi Republik Indonesia, 2011)
What it means by “under state control” on article 33 point (2) and (3) of UUD 1945, should not be interpreted that the state will control totally the entire economic activities that serve the public basic; the state is not a company refers to democratic economy of Indonesia which hinder monopoly on business by any state or etatism (state monopoly). The precise understanding of “under state control“ is state responsibility to manage and drive the economy regulation correctly.